2021
DOI: 10.30699/ajnmc.29.4.264
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spiritual Therapy on Resiliency of Hemodialysis Patients

Abstract: People with high resilience evaluate stressful events as more positive and controllable than people with low resilience. The aim of this study was to determine the effect of spirituality therapy on resilience of patients undergoing hemodialysis. Methods:The present study is a quasi-experimental study with two experimental and control groups. The statistical population of the study consisted of all patients undergoing hemodialysis referred to Imam Reza (AS) Hospital and Imam Ali (AS) Hospital in Amol, Iran. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…This is supported by Duran's research (2020) which states that there is a positive correlation between spiritual well-being and the resilience of hemodialysis patients. The same research results were also obtained by Sarijeh (2021) which stated that spiritual healing can increase the resilience of hemodialysis patients. Fulfilling the patient's spiritual needs can contribute to preventing mental disorders and improving the quality of life of patients with increase psychological resilience (Duran et al, 2020).…”
Section: Spiritual Well Beingsupporting
confidence: 70%
“…This is supported by Duran's research (2020) which states that there is a positive correlation between spiritual well-being and the resilience of hemodialysis patients. The same research results were also obtained by Sarijeh (2021) which stated that spiritual healing can increase the resilience of hemodialysis patients. Fulfilling the patient's spiritual needs can contribute to preventing mental disorders and improving the quality of life of patients with increase psychological resilience (Duran et al, 2020).…”
Section: Spiritual Well Beingsupporting
confidence: 70%
“…The findings of Fallah et al expressed the effect of spiritual intervention on reducing the tension and anxiety of these people and generally increased their general health (20). Kia et al reported that the resilience score increased after spiritual therapy, indicating the positive effect of spiritual therapy training in hemodialysis patients (21). In addition, Ebrahimi et al found a significant and high correlation between spiritual health and resilience in hemodialysis patients (22).…”
Section: Discussionmentioning
confidence: 99%
“…ESRD undergoing HD who use their religious beliefs and practices to cope with their lifelong survival treatment are less likely to experience psychological problems [23,93,94]. Spiritual therapy was effectively used with patients' receiving HD to improve their well-being [95], lifestyle [96], hope [97], resilience [98], and reducing their stress, anxiety, depression [99,100].…”
Section: Spiritual Practicesmentioning
confidence: 99%